Analisis Pengaruh Persepsi Pasien Tentang Mutu Pelayanan Terhadap Kepuasaan Pasien Rawat Jalan Unit Kedokteran Nuklir Instalasi Radiologi RSUP Dr. Kariadi Semarang - Nopriwan Nopriwan; Septo Pawelas Arso; Nurjazuli Nurjazuli (Jurnal Manajemen Kesehatan Indonesia, 2022)
ABSTRACTThe form of excellent service quality is often discussed in previous studies, including through indicators; tangibles, responsiveness, assurance, empathy and reliability. In this study, the service quality variable used is different from previous studies, namely using the Kennedy & Young theory, which uses indicators; availability, responsiveness, convenience and on time. The purpose of the study was to analyze the effect of patient perceptions of service quality on outpatient satisfaction of the nuclear medicine unit at the radiology installation of RSUP Dr. Kariadi Semarang. This type of research is observational with a quantitative approach, namely research that intends to test hypotheses. The research analysis unit is an outpatient who comes to get services from the nuclear medicine unit at the radiology installation of RSUP Dr. Kariadi Semarang in February 2022, as many as 314 patients, a sample size of 86 respondents was taken through simple random sampling.The results show that: the service quality variable affects the overall satisfaction variable, with an R2 value of 0.389. The service quality variable has an effect on the expectation variable with an R2 value of 0.456. The service quality variable affects the experience variable with an R2 value of 0.454. The conclusion of this study is that the service quality variable has a positive effect on patient satisfaction in the Outpatient Nuclear Medicine Unit, Radiology Installation, Dr. Kariadi Semarang.